Entrepreneurship Education Analysis and Planned Behavior Theory in Triggering Entrepreneurial Intentions Among Students - Unang Toto Handiman; Shita Lusi Wardhani; Ahmad Hidayat Sutawijaya; Dinar Nur Affini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
The purpose of this study was to analyze the Planned Behavior Theory and entrepreneurship education in triggering students' entrepreneurial intentions. This research was conducted at Mercu Buana University. The respondents of this study were students of the Faculty of Economics and Business, with a total sample of 250 student respondents. This study uses quantitative methods. The data collection technique used the snowball technique. Data processing uses a statistical model of Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of SMART PLS software. The study found that Entrepreneurship education has a significant influence on Attitude Toward Behavior, Subjective Norms, Perceived Behavioral Control and entrepreneurial intentions. Attitude Toward Behavior has a a significant effect on entrepreneurial intentions. Subjective Norms and Perceived Behavioral Control has no significant effect on entrepreneurial intention. Entrepreneurship education with Attitude Toward Behavior, Subjective Norms and Perceived Behavioral Control simultaneously has a moderate influence on entrepreneurial intentions.